Effect of Reduction of Pollutant Emissions on the Productivity Performance of Regional Canadian Pulp and Paper Industries - Yang, Shiqi (Université d'Ottawa | University of Ottawa, 2018)
In our study, the prod uclivily performance of the Canadian pul p and paper industry is compared with respect to the choice of measurement for desirable output, the length of lime period and with or without pollutant outputs. Input distance function can easily incorporate the non-marketable outputs of biological oxygen demand (BOD) and total suspended solids (TSS) on a quantity basis. This environmentally sensitive approach provides better producti vi ty performance for all regions, indicating the need for adjusting the conventional approach lhal ignores the poll utant outputs. The results abo indicate that indulitrial technological progress is different in different regions due lo variations in regional industry output and technology. Key words: input distance function, productivity performance, technical change, efficiency, pollutant outputs, pollutant abatement, waler effluent, pulp and paper industry.